THE EXPRESSIVE ILLOCUTIONARY ACTS IN “THUMBELINA” SHORT STORY ADAPTED BY SUE REID: A PRAGMATIC STUDY (English Literature Study Program of Universitas Kebangsaan Republik Indonesia, 2024)
This research is entitled “The Expressive Illocutionary Acts in “Thumbelina” Short Story adapted by Sue Reid: A Pragmatic Study”. Expressive means a kind of expressions, such as thanking, praising and blaming. The data of this research are gathered through reading Thumbelina short story and classify the data of expressive illocutionary acts. Descriptive qualitative research is applied in this research to describe, analyze and interpret expressive illocutionary acts which occurred in Thumbelina short story. The related theory applied in this research is (Searle, 1979) to determine expressive illocutionary acts in Thumbelina short story. Based on the data, there are 11 expressive illocutionary acts in the story, namely 6 in praising act, 2 in criticizing act and 3 in thanking act. The result of this research show that praising act is the most dominant expressive illocutionary act in the story and it is followed by thanking act and criticizing act. Keywords: Expressive; Illocutionary Act; Short Story